On the role of higher alcohols in the characterization of cachaça (Research, Society and Development, 2020)
There is a growing interest in chemical markers for the identification and certification of cachaça as a cane spirit produced in Brazil. It is known that the higher alcohols that are usually analyzed (propyl alcohol, Isobutyl alcohol and isoamyl alcohol) occur in all alcoholic beverages (fermented and distilled), but the relative proportions can vary markedly according to the peculiarities of the raw material and the production process. In this work, the contents of higher alcohols in 300 samples of alembic cachaça were compared, 220 from the state of Minas Gerais and 80 from other states, as well as three samples of industrial cachaça and 14 samples of whiskeys of various brands. The typical range of total higher alcohols in cachaça was 180-360 mg/100 mL ethanol. Cachaça containing higher alcohol concentrations greater than 360 mg/100 mL ethanol do not comply with Brazilian legislation. However, cachaças with higher alcohols concentrations below 180 mg/100 mL ethanol, as was found in one of the industrial cachaças, signify adulteration, for example, by mixing with fuel alcohol. The C4/C5 ratio varied less than the C3/C5 ratio, being consistently within the range of 0.20-0.50. In the whiskeys analyzed, the concentrations of higher alcohols were in the range of 160 and 270 mg/100 mL. Therefore, this parameter would not assist in differentiating between cachaça and whiskey. But the C4/C5 ratio was consistently different, being always greater than 0.50 for the whiskeys. Thus, the routine analysis of higher alcohols provides useful information both for tracking possible fraud and for assessments related to the identity or origin of cachaça.